Rufous‐capped Warblers Basileuterus rufifrons show seasonal, temporal and annual variation in song use. (22nd September 2018) - Demko, Alana D.; Mennill, Daniel J.
Abstract : In the majority of songbird species, males have repertoires of multiple song types used for mate attraction and territory defence. The wood‐warblers (family Parulidae) are a diverse family of songbirds in which males of many migratory species use different song types or patterns of song delivery (known as 'singing modes') depending on context. The vocal behaviour of most tropical resident warblers remains undescribed, although these species differ ecologically and behaviourally from migratory species, and may therefore differ in their vocal behaviour. We test whether male Rufous‐capped Warblers Basileuterus rufifrons use distinct singing modes by examining song structure and context‐dependent variation in their songs. We recorded multiple song bouts from 50 male Warblers in a Costa Rican population over 3 years to describe seasonal, diel and annual variation in song structure and vocal behaviour. We found that Rufous‐capped Warbler songs are complex, with many syllable types shared both within and between males' repertoires. Males varied their song output depending on context: they sang long songs at a high rate at dawn and during the breeding season, and shortened songs in the presence of a vocalizing female mate. Unlike many migratory species, Rufous‐capped Warblers do not appear to have different singing modes; they did not change the song variants used or the pattern of song delivery according to time of day, season or female vocal activity. Our research provides the first detailed vocal analysis of any Basileuterus warbler species, and enhances our understanding of the evolution of repertoire specialization in tropical resident songbirds.